Seasonal variation, treatment outcome, and its associated factors among the snakebite patients in Somali region, Ethiopia - Abdullahi, Ahmed; Yusuf, Nejib; Debella, Adera; Eyeberu, Addis; Deressa, Alemayehu; Bekele, Habtamu; Ketema, Indeshaw; Abdulahi, Ibsa Mussa; Weldegebreal, Fitsum (Frontiers in Public Health, 2022)
Abstract Background: Snakebite is a major cause of mortality and morbidity in many areas, particularly in the rural tropics, and is a major public health problem around the world. It also imposes significant economic burdens on snakebite victims due to treatment-related expenses and lost productivity. Objective: The purpose of this study was to assess seasonal variation, treatment outcomes, and its associated factors among snakebites patients in Denan health center in the Somalia region, Ethiopia from September 10 to 30, 2020 Method: A Facility based cross-sectional study was conducted from September 10 to 30, 2020 among 430 patients registered in Denan health center for snakebite between September 1, 2015- August,302020. Data were collected using a pre-tested structured checklist from the patient cards. Data were entered into Epidata version 3.1 and analyzed using SPSS version 22 (IBM SPSS Statistics, 2013). The prevalence was reported by proportion with 95% Confidence Interval (CI) and summary measures. Predictors were assessed using a multivariable logistic regression analysis model and reported using an adjusted odds ratio with 95%CI. Statistical significance was declared at p-value <0. 05. Result: The overall prevalence of poor outcomes of venomous snakebites was 45.76 % (95% CI:41.2%.52.3%). Study participants with an age of Less than 10 years old (AOR=4.63; 95%CI: 5.13,11.38), age between 10-30 years old (AOR=2.42; 95%CI: 1.83,9.30), arrival times which greater than or equal to 6 hours (AOR=2.37; 95%CI: 1.39,4.05). timing of snakebite (AOR=0.49;95%CI:0.31-0.77) were factors found to be significantly associated with outcome variables. Conclusion: According to this study, more than two in every five snake bites patients have a poor outcome. Designing appropriate engagement of public health education about snakebite prevention technics, particularly during rainy seasons and establishment of appropriate case management protocol is strongly recommended, as well as increasing the accessibility or availability of antivenoms, will undoubtedly have a significant impact on the reduction of mortality and disability related to that of the snake bites and poor access to health services increases snake bite-related morbidity and mortality; therefore, effective public health actions are warranted Keywords: Treatment outcome, snakebites, anti-venom, associated factors, Ethiopia.